Modified Atmosphere Storage Extends the Shelf Life of 'Nam Dok Mai Sri Tong' Mango Fruit. Issue 3 (2nd July 2020) - Phakdee, Nutchanat; Chaiprasart, Peerasak
ABSTRACT: Investigation of modified atmosphere packaging (MAP) on changes of fruit quality during cold storage and shelf life extension in mango was conducted with MAP using white ethylene absorbing bag (WEB) and green absorbing bag during storage at 15°C for 30 days. The results found that the mangoes kept in WEB maintained their texture and appearance better than those in package without a plastic bag. Mangoes stored in WEB were more firm than those stored in air (normal atmosphere) during 30 days of storage and could delay the ripening and maintained the quality of the fruits, while the fruit packed without plastic bags extended the shelf life for 24 days. The MAP retarded the ripening process and delayed color development of the mango fruit compared to the mangoes without packing during the cold storage. In particular, WEB effectively reduced respiration rate and weight loss of the fruits stored at 15°C for 30 days. This MAP maintained a higher titratable acidity and firmness of peel and pulp in the mango fruits, while the activities of polygalacturonases in the pulp were reduced. Comprehensive quality analysis indicated that this MAP was the most effective method for improving the quality of mango fruits and extension of shelf life under the cold storage.